The poetics of evil: toward an aesthetic theodicy - Tallon, Philip (Oxford University Press, 2012)
Aesthetics and the scope of theodicy -- Aesthetics and theological insight -- Fearful symmetry : theodicy and cosmic harmony -- Poetic injustice : theodicy and tragic vision -- The monsters and the critics : theodicy and horrendous evils